Automated Reasoning 5th International Joint Conference, IJCAR 2010, Edinburgh, UK, July 16-19, 2010. Proceedings - Giesl, J<U+00fc>rgen.; Hh̃nle, Reiner. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 5th International Joint Conference on Automated Reasoning, IJCAR 2010, held in Edinburgh, UK, in July 2010 as part of the Federated Logic Conference, FLoC 2010.The 28 revised full research papers and 12 revised system descriptions presented together with 1 full paper and 2 abstracts of invited talks were carefully reviewed and selected from 63 full paper and 26 system description submissions. The papers address the entire spectrum of research in automated reasoning and are organized in topical sections on logical frameworks and combination of systems; description logic; higher-order logic; verification; first-order logic; non-classical logic; induction; decision procedures; arithmetic; applications; and termination.